WP1-15 Computer-assisted versus manual planning for stereotactic brain biopsy: retrospective comparative pilot study. Issue 3 (14th February 2019) - Marcus, HJ; Vakharia, VN; Sparks, R; Rodionov, R; Kitchen, N; McEvoy, A; Miserocchi, A; Thorne, L; Ourselin, S; Duncan, JS
Abstract : Objectives: Stereotactic brain biopsy is among the most common neurosurgical procedures. Planning a safe surgical trajectory requires careful attention to a number of features including: traversing the skull perpendicularly; avoiding critical neurovascular structures; and minimising trajectory length. The aim of this study was to develop a platform, SurgiNav, for automated trajectory planning in stereotactic brain biopsy. Methods: A prospectively maintained database was searched between February and August 2017 to identify all adult patients that underwent stereotactic brain biopsy in whom post-operative imaging was available. In each case, the standard pre-operative T1-weighted gadolinium-enhanced MRI was used to generate models of the cortex and vasculature. A surgical trajectory was then generated using automated computer-assisted planning (CAP) and metrics compared to the trajectory of the implemented manual plan (MP) using the paired T-test. Results: 15 consecutive patients were identified; who had a diagnostic biopsy and there were no immediate complications. Feasible trajectories were generated using CAP in 12 patients, and in these the mean trajectory length using CAP was comparable to MP (31.7 mm vs. 37.1 mm; p=0.3), and mean angle was similarly perpendicular from orthogonal (9.3° vs. 15.3° p=0.1), but the risk-metric was significantly lower (0.16 vs. 0.48; p=0.03). Conclusions: Computer-assisted planning for stereotactic brain biopsy appears feasible in most cases and may be safer in selected cases.